Relation of mesangial IgA glomerulonephritis to polymorphism of immunoglobulin heavy chain switch region. - Demaine, A G (1988)
We have investigated the switch regions of Ig heavy chain genes of patients with IgA glomerulonephritis (IgA-GN) using restriction fragment length polymorphism (RFLP) analysis. Genomic DNA from patients and controls was digested with the restriction endonuclease Sst I and transferred to nylon membranes using the Southern blot procedure and hybridized with a probe homologous to the switch region of the Ig C mu gene (S mu) which detects RFLPs in both S mu and the switch region of the Ig C alpha 1 gene (S alpha 1). A significant decrease in the frequency of the 2.6;2.1 kb heterozygous S mu phenotype was found in patients with IgA-GN (P = 0.003). With respect to the S alpha 1 region, there was a significant increase in the frequency of the 7.4 kb S alpha 1 phenotype (P = 0.002). In addition, a significant increase in the frequency of the 7.4 kb S alpha 1 allele was found (P = 0.0002). These results suggest that gene(s) within the Ig heavy chain loci may be important in the pathogenesis of IgA-GN.